Implementation Evaluation of Information Technology in the New Normal Era Using Cobit 2019 Method - ., Surahmat; Ajismanto, Fahmi (KnE Social Sciences, 2023)
This research is a continuation of the previous research on Information Technology Governance Analysis of STMIK Palcomtech in the New Normal Era Using Cobit 2019 where the measurements carried out are the stages of 11 factors design Tool Kit Cobit 2019. The results of the study included 13 important processes in the domain that must be considered in STMIK Palcomtech including EDM03, APO08, DSS05 EDM02, APO04, APO09, APO12, APO13, BAI01, BAI02, BAI03, BAI06, MEA03. This research aims to evaluate the application of information technology used by STMIK Palcomtech focusing on the application of information technology applied based on the needs of the company and the strategy of the impact of COVID 19, which uses the Goal cascade framework Cobit 2019. Use qualitative method by spreading questionnaires in accordance with the domain that has been determined to students then continued with the measurement of maturity level so that current conditions are obtained and then continued gap analysis. The results of this study showed the average maturity level is at level 3 and the result of the gap level then the lowest value is a priority to prioritize new development then to the next domain to achieve the expected value in the domain Level. Keywords: information technology, COBIT, governance analysis